2012
DOI: 10.1002/tee.21715
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of tongue–artificial nipple contact pressure during infant sucking

Abstract: To clarify the motor function of the infant tongue during sucking, we developed an artificial nipple that contained multiple small built‐in force sensors integrated with a PC‐based system which is capable of measuring tongue–artificial nipple contact pressures in real time. The force sensor is a cantilever structure with a small, thin stainless steel beam where an all‐purpose foil strain gauge is attached to the surface of the beam. An artificial nipple made of an elastomer containing these sensors is connecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 7 publications
0
9
0
1
Order By: Relevance
“…Compression setting 1 and rotation setting 2 (C1R2) and compression setting 2 and rotation setting 1 (C2R1) may mimic the tongue pressure exerted at the apical portion of the tongue during breastfeeding, reported clinically as 108-222 KPa 6 . Compression setting 2 and rotation setting 2 (C2R2) may mimic that of the posterior portion of the tongue since this as has been measured by Niikawa et al 6 . to range from 231-294 KPa.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…Compression setting 1 and rotation setting 2 (C1R2) and compression setting 2 and rotation setting 1 (C2R1) may mimic the tongue pressure exerted at the apical portion of the tongue during breastfeeding, reported clinically as 108-222 KPa 6 . Compression setting 2 and rotation setting 2 (C2R2) may mimic that of the posterior portion of the tongue since this as has been measured by Niikawa et al 6 . to range from 231-294 KPa.…”
Section: Resultsmentioning
confidence: 95%
“…Based on clinical measurements by Niikawa et al., 6 the sensor measurements indicate that the various settings each were exerting pressures on the sensor separately physiologically relevant for tongue strength of young infants. Pressure is shown to vary due to tongue contact location, infant age, and infant birth-weight.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…These studies revealed that the tongue tends to form a bulge and moves from the tip to the root in a wave-like manner. In this study, to assess the tongue movements, including the above-mentioned peristalsis-like movement, we measured the contact force between the tongue-and an artificial nipple using cantilever force sensors ('Artificial Nipple A' described below) [8][9][10]. As a result of the research so far, we have obtained the output waveforms of phase differences, which showed the peristalsis-like movement, as well as about two periods of sucking per second as in visual observation studies.…”
Section: Introductionmentioning
confidence: 99%